The Relationship Between Cardiovascular Disease Risk Score and Postoperative Delirium: The PNDABLE Study - Wang, Jiahan; Wang, Li; Tang, Xinhui; Wang, Fei; Liu, Siyv; Wu, Xiaoyue; Dong, Rui; Lin, Xu; Wang, Bin; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Objective: We aimed to investigate the relationship between Framingham Heart Study general cardiovascular disease risk score (FHS-CVD risk score) and postoperative delirium (POD) among patients who had unilateral total knee arthroplasty performed under epidural anesthesia. Furthermore, we examined whether such a hypothesised relationship was mediated by the cerebrospinal fluid (CSF) biomarkers. Methods: A total of 750 participants were included in the current study. And the data was drawn from the database obtained from the Perioperative Neurocognitive Disorder And Biomarker Lifestyle (PNDABLE) study. Linear regression analysis was performed to examine the relationship between FHS-CVD risk score and the POD CSF biomarkers. Logistic regression was used to analyze the relationship between FHS-CVD risk score, POD CSF biomarkers and POD incidence. The proposed mediating effect of CSF biomarker was evaluated using Mediation analysis with 10,000 bootstrapped iterations. The receiver operating characteristic (ROC) curve is chosen as the evaluation metric for assessing the efficacy of FHS-CVD risk score in predicting POD. Results: In the PNDABLE study, the overall incidence of POD was 22.9%, with 37.2% in the higher vascular risk group and 7.9% in the lower vascular risk group. Multiple linear regression models showed that higher preoperative FHS-CVD risk score were positively correlated with CSF T-tau (β = 0.218, P=0.015) and P-tau level (β = 0.309, P<0.001) in the higher vascular risk group. After adjusted for age (40-90), gender, education, MMSE, smoking history, drinking history, hypertension, diabetes and the presence of CHD (cardiovascular heart disease), results of the logistic regression analysis demonstrated FHS-CVD risk score (OR=1.142, 95%CI 1.017-1.282, P=0.025) and the two biomarkers: T-tau (OR=1.005, 95%CI 1.004-1.007, P<0.001) and P-tau (OR=1.045, 95%CI 1.029-1.062, P<0.001) were identified as the risk factors. Mediation analyses revealed that the association between FHS-CVD risk score and POD was partially mediated by T-tau (proportion: 31.6%) and P-tau (proportion: 23.6%). The predictive power of FHS-CVD risk score was validated by the ROC curve with an AUC of 0.7364. Conclusion：Higher vascular risk score is one of the preoperative risk factors for POD, which is partly mediated by CSF biomarker tau protein.